The phylogeny and ontogeny of autonomic control of the heart and cardiorespiratory interactions in vertebrates - Taylor, Edwin W. [UNESP]; Leite, Cleo A. C.; Sartori, Marina R.; Wang, Tobias; Abe, Augusto S.; Crossley, Dane A. (Company of Biologists Ltd, 2014)
Heart rate in vertebrates is controlled by activity in the autonomic nervous system. In spontaneously active or experimentally prepared animals, inhibitory parasympathetic control is predominant and is responsible for instantaneous changes in heart rate, such as occur at the first air breath following a period of apnoea in discontinuous breathers like inactive reptiles or species that surface to air breathe after a period of submersion. Parasympathetic control, exerted via fast-conducting, myelinated efferent fibres in the vagus nerve, is also responsible for beat-to-beat changes in heart rate such as the high frequency components observed in spectral analysis of heart rate variability. These include respiratory modulation of the heartbeat that can generate cardiorespiratory synchrony in fish and respiratory sinus arrhythmia in mammals. Both may increase the effectiveness of respiratory gas exchange. Although the central interactions generating respiratory modulation of the heartbeat seem to be highly conserved through vertebrate phylogeny, they are different in kind and location, and in most species are as yet little understood. The heart in vertebrate embryos possesses both muscarinic cholinergic and beta-adrenergic receptors very early in development. Adrenergic control by circulating catecholamines seems important throughout development. However, innervation of the cardiac receptors is delayed and first evidence of a functional cholinergic tonus on the heart, exerted via the vagus nerve, is often seen shortly before or immediately after hatching or birth, suggesting that it may be coordinated with the onset of central respiratory rhythmicity and subsequent breathing.
Keywords: Autonomic nervous system; Parasympathetic tonus; Cardiorespiratory interaction; Heart rate variability; Respiratory sinus arrhythmia; Ontogeny; Vertebrate